2014
DOI: 10.1177/1049909114550391
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Early Palliative Care for Patients With HIV

Abstract: Increasingly clinicians are using palliative care to address the symptomatic and psychosocial effects of disease often missed by routine clinical care, termed "early" palliative care. Within an inner-city medical center, we began a program to integrate early palliative care into HIV inpatient care. Patient symptom burden and desired services were assessed and compared to provider perceptions of patient's needs. From 2010-2012, 10 patients, with a median CD4+ T-cell count of 32.5 cells/μL, and 34 providers comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…But in spite of high-quality medical treatment, PLWH often experience inadequate symptom control (Harding et al, 2010; Karus et al, 2005; Merlin et al, 2012). The aging of the PLWH population, their risks for other chronic conditions, and their needs for better symptom management suggest a critical need for palliative care services for PLWH with other chronic conditions (PLWH/OCC; Lofgren et al, 2015; Ruiz & Cefalu, 2011). …”
mentioning
confidence: 99%
“…But in spite of high-quality medical treatment, PLWH often experience inadequate symptom control (Harding et al, 2010; Karus et al, 2005; Merlin et al, 2012). The aging of the PLWH population, their risks for other chronic conditions, and their needs for better symptom management suggest a critical need for palliative care services for PLWH with other chronic conditions (PLWH/OCC; Lofgren et al, 2015; Ruiz & Cefalu, 2011). …”
mentioning
confidence: 99%
“…A benefit of early palliative care is the care team’s ability to build rapport and trust that will allow a deeper holistic assessment of the patient (Back et al, 2014; Yoong et al, 2013). The relationship that is built will allow the team to see that the patient may have greater needs than just symptom control and improve the patient’s willingness to accept the care team’s recommendations (Lofgren et al, 2015). Once a rapport is established, the palliative care team can act as a security blanket for the patient and family (Hannon, Swami, Rodin, Pope, & Zimmermann, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Within the HIV population, one author suggested that EPC should be de ned by clinical criteria, speci cally a CD4 T-cell in the 300-400 cells/mL. 110 Webel and colleagues (2019) de ned EPC as care initiated early in the disease trajectory for HIV patients. When examining the role of EPC among patients with COPD, authors based their de nition on advanced disease stage (stage III or IV based on the GOLD criteria).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%